Application of soda pulping method in cellulose extraction process from pineapple leaf - Mohamad Shaiful, Abdul Karim; Norazwina, Zainol; N. I. A., Abu Hassan As’ari; Nur Shahira, Mat Hussain; N.H., Aziz (Elsevier Ltd, 2022)
This paper briefly discusses the utilization of agricultural waste in developing valuable materials, especially in material engineering fields. Pineapple is known as one of the most common plants found in every plantation in Malaysia. The edible pineapple fruit was the only part being used, while the other parts were categorized as agricultural waste. Pineapple leaves consisted of high cellulosic materials that can be manipulated into developing various applications as raw materials. Identifying the suitable processing parameters and their desired range for maximum cellulose extraction is crucial for a better yield. Hence, this study aimed to determine the effect of pulping time on cellulose extraction through the soda pulping method and its corresponding permittivity value. The experiment was performed based on the one-factor analysis by varying only one factor while keeping the other factors constant. In this study, pulping times (15 to 75 min) were the factor of interest, with the pineapple leaves to soda ratio (PL:S), soda concentration, and temperature were fixed at 1:5, 10 wt%, and 60℃, respectively. The extracted cellulose content was analyzed by Kurschner's and Hanack's methods, while the permittivity of cellulose was measured in G-band using waveguide technique within the frequency of 4 to 6 GHz. Based on the finding, the best condition for cellulose extraction by soda pulping method was at 60 min pulping times, 1:5 PL:S, 10 wt% soda concentration, and 60℃ temperatures, which give rise to 31.9% cellulose content and 5.239 permittivity value. Hence with the cellulose content and permittivity value obtained in this study, the soda pulping method can be adopted for cellulose extraction from pineapple leaves. The permittivity value of the cellulosic material in pineapple leaves suggests that the material could store energy suitable for capacitor applications.